Integrated water resources management in the 21st century revisiting the paradigm - Martinez-Santos, Pedro; Aldaya, Maite M.; Llamas, M. Ramon (CRC Press, 2014)
Integrated water resources management advocates a coordinated approach for managing water resources in a way that balances social and economic needs with concern for the environment. While potentially useful, integrated water management is also controversial. Supporters believe that the multi-dimensional nature of water can only be understood and managed from a holistic perspective, while critics often argue that integrated water management lacks suffi ciently well-defi ned rules for its practical implementation. This book, written by academics, users and practitioners, provides a down-to-earth approach to the ideal of integrated water resources management, drawing from conceptual frameworks and real-life practice to identify the key aspects that are yet to be resolved. As such, it examines the role of water accounting, food trade, environmental externalities and intangible values as key aspects whose consideration may help the water management community move forward. Overall, integrated water resources management is perceived to be a useful utopia, whose value lies more in the steps that need to be taken to make it a reality than in achieving its ever-elusive end goal.